COMMUNICATION PATTERNS OF RELIGIOUS MINORITY IN CULTURAL ADAPTATION IN CENTRAL ACEH REGENCY - Fachrur Rizha; Sutrisno Sutrisno; Julia Noviani (Profetik: Jurnal Komunikasi, 2020)
The majority of religious beliefs in Central Aceh Regency are Muslim. Only a few immigrants such as Chinese and Batak ethnic groups who have religion other than Islam. As a minority group, cultural differences, religious symbols and rituals tend to attract attention and sometimes can cause ripple effects that lead to dispute in the community. This study aimed to describe the communication patterns developed by religious minorities in adapting to the culture of indigenous Muslims in Central Aceh Regency. This study used qualitative research with subject representatives of religious organizations, representatives of religious leaders, and people with minority religious backgrounds in Central Aceh Regency. The results showed that religious minorities live side by side with the indigenous Muslim community. Communication patterns built by religious minorities in social interaction are carried out in two models, interpersonal and group communication. In interpersonal communication, religious minorities prioritize a cultural approach, including by using language, culture and customs that are inherent in indigenous Muslims. While, in group communication, religious minorities put forward group representatives in the Forum for Religious Harmony (FKUB) in building harmony and cultural adaptation in order to avoid potential disputes in the future.